KARAKTERISTIK FISIK, KIMIA, DAN ORGANOLEPTIK FLAKES DARI BEKATUL BERAS, TEPUNG KACANG HIJAU, DAN TEPUNG UBI JALAR KUNING DAN PENAMBAHAN KUNING TELUR (Characteristisc of Physical, Chemical, and Organoleptic of Flakes of Rice Bran, Green Bean Flour, and Ye - Meinar W. Simbolon; Herla Rusmarilin; Elisa Julianti (Jurnal Rekayasa Pangan dan Pertanian, 2017)
ABSTRACT The aim of this research was to find the effect of ratio of rice bran, green bean flour, and yellow sweet potato flour and addition of egg yolk on the characteristics of physical and chemical properties of flakes. The research was using completely randomized design with two factors. The first factor, was ratio of rice bran, green bean flour, and yellow sweet potato flour (0% : 40% : 60%,   10% : 30% : 60%, 20% : 20% : 60%, dan 30% : 10% : 60%). The second factor, was additional of egg yolk (2,5%, 5%, and 7,5%). Parameters analyzed were moisture content, ash content, crude fiber content, protein content, fat content, carbohydrate content, water absorption, resilience crispness in milk, texture test, colour rendering index, hedonic organoleptic values of flavor, taste, and colour and organolptic score of texture. The results showed that the ratio of rice bran, green bean flour, and yellow sweet potato flour had highly significant effect on moisture content, ash content, fat content, protein content, crude fiber content, and carbohydrate content, and had significant effect on colour rendering index and organoleptic value of taste. The additional of egg yolk had highly significant effect on moisture content and fat content, and had significant effect on protein content and carbohydrate content. Interaction of the two factors had highly significant effect on moisture content, fat content, and carbohydrate content. The ratio of rice bran, yellow sweet potato flour, and yellow sweet potato flour of (10%:30%:60%)  and  addition of egg yolk of (5%) produced the best flakes. Keywords : rice bran, green bean flour, yellow sweet potato flour, egg yolk, flakes ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh perbandingan bekatul beras, tepung kacang hijau, dan tepung ubi jalar kuning dan penambahan kuning telur terhadap karakteristik sifat fisik dan kimia flakes. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan 2 faktor. Faktor 1 perbandinan bekatul beras, tepung kacang hijau, dan tepung ubi jalar kuning (0% : 40% : 60%, 10% : 30% : 60%, 20% : 20% : 60%, dan 30% : 10% : 60%) dan penambahan kuning telur (2,5%, 5%, dan 7,5%). Parameter yang dianalisa adalah kadar air (%), kadar abu (%), kadar serat kasar (%), kadar protein (%), kadar lemak (%), kadar karbohidrat (%), daya serap air, ketahanan kerenyahan dalam susu, uji tekstur, indeks warna (°Hue), uji hedonik organoleptik (aroma, rasa dan warna) dan uji skor tekstur. Hasil penelitian menunjukkan bahwa perbandingan bekatul beras, tepung kacang hijau, dan tepung ubi jalar kuning memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar abu, kadar lemak, kadar protein, kadar serat kasar, dan kadar karbohidrat, berbeda nyata terhadap indeks warna dan uji organoleptik hedonik rasa. Penambahan kuning telur memberikan pengaruh berbeda sangat nyata terhadap kadar air dan kadar lemak, berbeda nyata terhadap kadar protein dan karbohidrat. Interaksi kedua faktor memberikan pengaruh berbeda sangat nyata terhadap kadar air, lemak, dan kadar karbohidrat. Perbandingan bekatul beras, tepung kacang hijau, dan tepung ubi jalar kuning (10%:30%:60%) dan penambahan kuning telur (5%) menghasilkan flakes dengan mutu terbaik.   Kata kunci : bekatul beras, tepung kacang hijau, tepung ubi jalar kuning, kuning telur, flakes